Blockchain in Indonesia University: A Design Viewboard of Digital Technology Education - Dudhat, Amitkumar; Lestari Santoso, Nuke Puji; Henderi; Santoso, Sugeng; Setiawati, Riri (Pandawan, 2021)
The challenge that has often occurred in recent years is making access to education using a different learning process path. The presence of technology now provides solutions to problems that often occur such as communication, accessing information, and business or cooperation. Blockchain is a technology that develops an evaluation model for itineraries in the learning process, both individually and in bulk. Currently the Edublocs project has been designed and implemented, which combines elements of peer-to-peer learning and the teaching team. The aim of the Edublocs project is to simplify the process of designing and implementing a system for recording activity results through blockchain technology. This ongoing project is in the process of evaluation. Conforming to some design elements as well as experimental implementation in the context of higher education enables us to further indicate the sustainability and relevance of the application of blockchain technology in education.